2014
DOI: 10.1152/ajpheart.00986.2013
|View full text |Cite
|
Sign up to set email alerts
|

Role of estrogens and age in flow-mediated outward remodeling of rat mesenteric resistance arteries

Abstract: tance arteries, a chronic increase in blood flow induces hypertrophic outward remodeling. This flow-mediated remodeling (FMR) is absent in male rats aged 10 mo and more. As FMR depends on estrogens in 3-mo-old female rats, we hypothesized that it might be preserved in 12-mo-old female rats. Blood flow was increased in vivo in mesenteric resistance arteries after ligation of the side arteries in 3-and 12-mo-old male and female rats. After 2 wk, high-flow (HF) and normal-flow (NF) arteries were isolated for in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…FMR has been shown to be reduced by hypertension,58, 59 diabetes mellitus,60, 61 and aging 11, 62. More important and rather unexpectedly, we previously reported that FMR depends on the presence of ERα15, 63 and could contribute to the better resistance to ischemia/necrosis of female compared with male mice. Herein, we report that ERα MISS is also dispensable to mediate this beneficial action of estrogens.…”
Section: Discussionmentioning
confidence: 77%
“…FMR has been shown to be reduced by hypertension,58, 59 diabetes mellitus,60, 61 and aging 11, 62. More important and rather unexpectedly, we previously reported that FMR depends on the presence of ERα15, 63 and could contribute to the better resistance to ischemia/necrosis of female compared with male mice. Herein, we report that ERα MISS is also dispensable to mediate this beneficial action of estrogens.…”
Section: Discussionmentioning
confidence: 77%
“…For example, mRNA transcript and protein of Nox1, Nox2, Nox4, p22 phox , p47 phox , p67 phox and Rac1/2 subunits were detected in mouse and rat mesenteric resistance arteries [19,58,60,66,67,71], where Noxs are implicated in structural and functional alterations in response to distinct stimuli [17,72,73]. In mouse coronary arteries, protein expression of Nox2 and its regulatory subunits p67 phox , p47 phox and p22 phox were reported [64].…”
Section: Systemic Microcirculationmentioning
confidence: 99%
“…Estrogens exert beneficial effects on the vasculature [ 25 ] and flow-mediated remodeling of mesenteric resistance arteries dependent on the activation of the estrogen receptor alpha by estrogens [ 18 , 26 , 27 ]. Although women are better protected than men against cardiovascular diseases before menopause [ 28 ], the WHI study led to the interruption of estrogen substitution treatments in post-menopausal women [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of resistance arteries to enlarge their diameter in response to a chronic increase in blood flow in vivo is strongly reduced in rat models of aging [ 16 18 ], hypertension [ 19 , 20 ] and diabetes [ 11 , 21 , 22 ] although maintained in obesity [ 23 ]. Flow-mediated outward remodeling does not occur in male rats aged 10 months or more [ 16 , 17 , 24 , 25 ] whereas it is maintained in female rats aged 12 to 18 months [ 26 ].…”
Section: Introductionmentioning
confidence: 99%